Learning stories: An instrument to document and observe interests, activities and wellbeing of preschool children - Karlsdóttir, Kristín; Hreinsdóttir, Anna Magnea (Menntavísindasvið Háskóla Íslands, 2016)
The article describes an action research project performed in eight preschools in one of the neighbouring municipalites of Reykjavik. Twenty-three preschool teachers, the team leaders of all classroom divisions in all eight schools, took part in the study along with the authors of this article: an assistant professor at the University of Iceland and the preschool representative of Garðabær. The aim of the study was to support the preschool teachers in their first steps of documenting children’s learning stories and to develop methods to assess children’s wellbeing and learning. The data describes how the teachers developed their methods of documenting children’s learning stories in relation to their wellbeing and learning applying such stories as tools of assessment in collaboration with children, parents and other educators, and how they approached children’s views to be able to support their learning and plan preschool activities in relation to this information. Information was gathered on what was useful and on the hindrances the participants met. According to the Icelandic National Curriculum for Preschools, teachers in each preschool shall plan and adopt an appropriate working procedure and develop a variety of methods to gather information on children’s learning and wellbeing. To gain better understanding and insight into children’s learning processes and their areas of interest and strengths, the information should be reflected on in collaboration with children, parents and other educators and used to assess the preschool practice. The learning story approach originating from New Zealand and widely used there is among the methods which have been developed to document children’s learning by focusing on their interest, abilities and competence. When developing children’s learning stories, teachers observe children as they take part in preschool activities, such as play and creative activities, and write narratives that the teachers reflect on together with children, parents and other educators to be able to ...